Management of Udar Vyadhi with Ayurveda with Special Reference to Ascites - Mishra, Reena Shivasgar; Chandurkar, Vivek (International Research Journal of Ayurveda & Yoga, 2023)
Udara roga means any etiology-related generalized abdominal distension or hypertrophy. Ascites is the most prevalent sign of liver malfunction, and despite the use of sophisticated medical equipment, there is still no proven method of curing ascites in patients as mentioned in Acharya if it is not treated the patient will die soon. Modern therapies only offer temporary relief with time-dependent recurrence, yet fluid continues to build up in the abdominal cavity. Jalodara is one of the eight types of Udar roga described in Ayurveda. It is mentioned in all three brihatrayee texts (Charaka Samhita, Susruta Samhita, and Ashtanga Hridaya). In Ayurveda, Udara roga covers conditions such as gaseous distension, hepatosplenomegaly of various etiologies, intestinal blockage, and intestinal perforation in addition to ascites and fluid buildup in the peritoneal (common presentation is abdominal distension throughout). Its pathophysiology is thought to be primarily caused by mandagni. Udakavaha srotas and Ambu vaha srotas are mentioned in relation to Jalodara pathology in all three sources. Talu and kloma make up the moola (base) of Udakavaha srotas. In Ayurveda, kloma is a contentious subject. Some writers liken it to the pancreas. Jalodara is said to be caused by the dusti (fault) of udakavaha srotas or (kloma). Ayurvedic medicine offers relief in such circumstances without causing any negative side effects. Ayurvedic care of Udar (ascites) with medications such as provocation of digestion daily therapeutic purging, stimulants for hepatic function, and only milk diet that operates on the basis of the pathophysiology of ascites and by splitting down of pathogenesis produces good results in management. Cirrhosis of the liver is the most frequent cause of ascites in the developed world. Other causes include pancreatitis, TB, cancer, heart failure, and hepatic vein blockage. The highlighted mechanism in cirrhosis involved elevated portal blood pressure and blood vessel dysfunction. The true cause and severity of ascites have a significant impact on a person’s prognosis. This article discusses several Acharya treatments from an Ayurvedic perspective.